Comprehensive performance review of BDS-3 after one-year official operation. Issue 1 (1st January 2023) - Zhu, Yongxing; Zhang, Qinghua; Mao, Yue; Cui, Xianqiang; Cai, Changsheng; Zhang, Ruibin
Abstract: On July 31, 2020, the third generation BeiDou Global Satellite Navigation System (BDS-3) was officially put into service. Here we first reviewed the development history of BDS-3, and described the status of BDS-3 constellation, satellite signals, and ground tracking network. Then we expounded the 10 innovations in which BDS-3 differs from the other global satellite navigation systems. In addition, the latest service performance status of BDS-3 was displayed from a comprehensive perspective. The performance of BDS-3 was analyzed and evaluated from five aspects: constellation performance, observation data quality, spatial signal performance, PNT (Positioning, Navigation, and Timing) service performance, and precision positioning application. We used 14 indices to conduct comprehensive assessment of the BDS-3 service performance. Finally, the main direction of the next development of BDS was prospected.